Budaya Jawa dalam Cerpen Mencicipi Semesta Karya Riska Dyah Oktaviani - Kidungjati, Kedasih; Pranata, Gigih Bayu; Baihaqi, Imam (Kajian Bahasa dan Sastra (KABASTRA), 2023)
Literature is a form of creative activity in which there are cultural elements. Literature can be divided into written literature or oral literature. Meanwhile, culture is a way of life or living habits that develop in society and are passed down from generation to generation. Culture is formed from complex elements, namely religious systems, politics, customs, practices, language, buildings, clothing and works of art. A short story is a literary work written briefly that tells a conflict or event. This research aims to analyze Javanese culture contained in the short story entitled "Mencicip Semesta" by Riska Dyah Oktaviani. In conducting this research, researchers used qualitative descriptive research methods. The subject of this research is the short story "Mencicip Semesta" by Riska Dyah Oktaviani. This research focuses on Javanese culture contained in the short story "Mencicip Semesta" by Riska Dyah Oktaviani. The data source in this research is the short story "Mencicip Semesta" by Riska Dyah Oktaviani. Data collection is done using reading and note-taking techniques. The results of the research show that (1) The short story "Mencicip Semesta" contains Javanese culture, especially Solo and Yogyakarta. (2) The culture contained is the culture of kissing hands, traditional houses in the form of Rumah Joglo, traditional food in the form of Selat Solo and Gudeg, traditional performances and the use of Javanese.